2022
DOI: 10.1039/d2ra03716e
|View full text |Cite
|
Sign up to set email alerts
|

Ce and P123 modified layered double hydroxide (LDH) composite for the synthesis of polypropylene glycol monomethyl ether

Abstract: The application of recyclable heterogeneous catalysts in the production of polypropylene glycol monomethyl ether (MPPG) is of great significance to the green chemical industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…[ 23 ] As shown in Figure 1d, the CeO 2 NPs‐loaded LDH (denoted as LDH‐CeO 2 ) has been successfully synthesized in which the CeO 2 NPs can be clearly visulized to be attached on the surface of LDH, as also suggested by the corresponding fast Fourier transform (FFT) image showing the mixed patterns of both crystalline structures of CeO 2 NPs and LDH. [ 24 ] This TEM observation evidences the excellent dispersity of LDH‐CeO 2 in aqueous phase. The high‐angle annular dark‐field scanning transmission electron microscopy (HAADF‐STEM) images indicate the presence of CeO 2 NPs on the surface of LDH (Figure 1e), while the elemental mapping evidences the presence and uniform distributions of Mg, Al, Ce and O elements in the LDH‐CeO 2 (Figure 1e), where the distribution of Ce element is clearly overlapped with that of CeO 2 NPs observed in HAADF‐STEM.…”
Section: Resultsmentioning
confidence: 62%
“…[ 23 ] As shown in Figure 1d, the CeO 2 NPs‐loaded LDH (denoted as LDH‐CeO 2 ) has been successfully synthesized in which the CeO 2 NPs can be clearly visulized to be attached on the surface of LDH, as also suggested by the corresponding fast Fourier transform (FFT) image showing the mixed patterns of both crystalline structures of CeO 2 NPs and LDH. [ 24 ] This TEM observation evidences the excellent dispersity of LDH‐CeO 2 in aqueous phase. The high‐angle annular dark‐field scanning transmission electron microscopy (HAADF‐STEM) images indicate the presence of CeO 2 NPs on the surface of LDH (Figure 1e), while the elemental mapping evidences the presence and uniform distributions of Mg, Al, Ce and O elements in the LDH‐CeO 2 (Figure 1e), where the distribution of Ce element is clearly overlapped with that of CeO 2 NPs observed in HAADF‐STEM.…”
Section: Resultsmentioning
confidence: 62%
“…However, the FTIR results of the Cu/Ce@g-C 3 N 4 catalyst demonstrated that the Ce metal was present in the form of oxides (CeO 2 ) and its vibrations were identified at 500 cm −1 . 44…”
Section: Resultsmentioning
confidence: 99%
“…However, the FTIR results of the Cu/Ce@g-C 3 N 4 catalyst demonstrated that the Ce metal was present in the form of oxides (CeO 2 ) and its vibrations were identified at 500 cm −1 . 44 TGA Thermogravimetric analyses were conducted to examine the thermal stability, % mass decomposition and preparation mechanism of g-C 3 N 4 catalysts. 45 TGA curves of the precursor melamine and the as-prepared Cu/Ce@g-C 3 N 4 are shown in Fig.…”
Section: Ftirmentioning
confidence: 99%
“…As a result, the larger surface area allows for more active sites 11 , which are effective for removing various contaminants including heavy metals, organic dyes, and anions 12 , as well as catalyzing various reactions, including oxidation, hydrogenation, and acid-base catalysis 13 , LDHs often contain bimetallic active sites that increase the e ciency of electron transfer and the rate of free radical production, and are a promising substrate for catalytic reactions due to their unique properties, affordability, and ability to prevent metal leaching. [14][15][16][17][18] Lanthanides and actinides are the F elements that many researchers use these elements in the structure of LDHs today [19][20] . Cerium is the second and rarest earth element from the lanthanide series with the oxidation and reduction capability of various Ce 3+ /Ce 4+ electronic states 21,22 .…”
Section: Introductionmentioning
confidence: 99%